2023
DOI: 10.1002/ijc.34473
|View full text |Cite
|
Sign up to set email alerts
|

The evidence base of US Food and Drug Administration approvals of novel cancer therapies from 2000 to 2020

Abstract: Concerns have been raised that regulatory programs to accelerate approval of cancer drugs in cancer may increase uncertainty about benefits and harms for survival and quality of life (QoL). We analyzed all pivotal clinical trials and all non‐pivotal randomized controlled trials (RCTs) for all cancer drugs approved for the first time by the FDA between 2000 and 2020. We report regulatory and trial characteristics. Effects on overall survival (OS), progression‐free survival and tumor response were summarized in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Compared to other studies, we similarly found that the percentage of drug approvals based on OS was small, 19 and almost one‐third of approvals are via the accelerated pathway that requires post‐marketing studies 20 . However, our study extends these findings by evaluating the fate of these approvals to see how many provide further evidence of OS efficacy, even among drugs receiving accelerated approval.…”
Section: Discussionsupporting
confidence: 64%
“…Compared to other studies, we similarly found that the percentage of drug approvals based on OS was small, 19 and almost one‐third of approvals are via the accelerated pathway that requires post‐marketing studies 20 . However, our study extends these findings by evaluating the fate of these approvals to see how many provide further evidence of OS efficacy, even among drugs receiving accelerated approval.…”
Section: Discussionsupporting
confidence: 64%
“…While drug approvals are based on statistical significance of the endpoint achieved, this need not always be clinically significant. The average improvement in overall survival for 86 drugs approved between 2006 and 2017 was a paltry 2.5 months 28 …”
Section: Addressing Challenges In Access To Oncology Carementioning
confidence: 99%
“…The average improvement in overall survival for 86 drugs approved between 2006 and 2017 was a paltry 2.5 months. 28 With skyrocketing prices of cancer drugs and the modest benefits that these interventions add, it is important to define value-based care. The value of any therapeutic strategy is determined by the magnitude of clinical benefit balanced against its costs.…”
Section: Affordability and Pricing Of Oncology Medicinesmentioning
confidence: 99%
“…Moreover, many approved drugs that have been considered to be successful have been the subject of criticism by experts and available evidence. A considerable number are suggested to exert minimal effects, offering almost no benefit compared to previously approved drugs, or have been approved only based on surrogate end points ,, or flawed and limited evidence. ,,, Compared to placebo, many approved drugs probably offer at best only marginal benefit and may even lower a patient’s quality of life and survival. , , …”
Section: Introductionmentioning
confidence: 99%